Adaptive Fractional High‐order Terminal Sliding Mode Control for Nonlinear Robotic Manipulator under Alternating Loads. Issue 4 (1st July 2020) - Ahmed, Saim; Wang, Haoping; Tian, Yang
Abstract: In this study, trajectory tracking of robotic manipulators under varying loads with uncertainties and external disturbances is obtained by proposing model‐independent adaptive fractional high‐order terminal sliding mode control (AFO‐HoTSMC). The proposed AFO‐HoTSMC method is composed of an adaptive high‐order terminal sliding mode control integrated with fractional‐order (FO) control. An adaptive tuning control is utilised to evaluate the uncertain unknown dynamics of the system without relying on the prior knowledge of the upper bounds. FO control and HoTSMC are used to achieve the fast finite‐time convergence, chatter‐free control inputs, better tracking performance and robustness. The finite‐time stability of the overall system is investigated and derived from the Lyapunov stability criterion. Finally, to validate the effectiveness and robustness of the developed control method, comparative simulations with H ∞ ‐Adaptive control, intelligent PD (iPD), intelligent PID (iPID) and adaptive third‐order SMC (ATOSMC) are realized to demonstrate the performance of AFO‐HoTSMC.